A high-speed optical module internal connection optical adhesive and preparation method thereof
By using epoxy resin and modified hyperbranched polyether combined with nanobarium sulfate@silica nanomaterials in high-speed optical modules, the problems of poor bonding performance and high curing shrinkage are solved, and the problems of traditional optical adhesives are achieved. Low volatility, high durability, low refractive index and good bonding performance.
Patent Information
- Application Number
- CN202411160879.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Traditional optical adhesives have low bonding performance in high-speed optical modules, high curing shrinkage, high refractive index, poor light transmission, which affects optical performance, and has a long curing time and poor bonding performance.
Using epoxy resin as the matrix, combined with modified hyperbranched polyether and nanobarium sulfate@silica nanomaterials as reinforced fillers, the curing shrinkage and refractive index are reduced through dual curing of ultraviolet light and heat, and the transparency and bonding are improved. performance.
The optical glue is achieved with low volatility, high durability and good bonding strength, which reduces the curing shrinkage and refractive index, improves transparency and flexibility, and has a fast curing speed and excellent bonding performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical adhesives, and in particular to an optical adhesive for internal connection of a high-speed optical module and a preparation method thereof. Background Art
[0002] High-speed optical modules usually refer to integrated optical transceiver modules, which are composed of optical transmitters (TOSA, including lasers), optical receivers (ROSA, including photodetectors), main control circuit boards (PCBA), housings, and optical (electrical) interfaces. In the production and assembly of high-speed optical modules, optical adhesives play a vital role. Traditional optical adhesives (such as acrylic optical adhesives and polyurethane optical adhesives) have low bonding properties and relatively high shrinkage after curing. Optical adhesives based on epoxy resin have low volatility, will not pollute optical devices, and have excellent durability and high bonding strength.
[0003] In addition, in optical devices, it is also necessary to minimize light loss and maintain good optical performance of the device. However, general optical adhesives have a high refractive index and poor light transmittance, which leads to light loss in optical devices. Therefore, optical adhesives also need a lower refractive index and better light transmittance. In view of the above shortcomings of optical adhesives, epoxy resin optical adhesives with relatively low curing shrinkage can be used as the main body, and then fillers can be added to reduce the curing shrinkage of the optical adhesive and improve the transparency of the optical adhesive; the refractive index of the optical adhesive can be reduced by introducing polyethers with low refractive index and fluorinated segments; in addition, considering that a single curing method (such as UV curing, thermal curing, etc.) requires a long curing time and the bonding performance after curing is relatively poor, dual curing of UV light and heat can be used to improve the bonding performance and bonding speed of the optical adhesive. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-speed optical module internal connection optical adhesive and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An optical adhesive for connecting inside a high-speed optical module, comprising the following raw materials in parts by weight: 25-35 parts of bisphenol A epoxy resin, 8-15 parts of modified hyperbranched polyether, 2-4 parts of photoinitiator, 3-5 parts of curing agent, 10-20 parts of active diluent, 8-12 parts of reinforcing filler, 0.5-1 parts of antioxidant, and 0.2-0.5 parts of inhibitor;
[0007] The reinforcing filler is prepared by the following steps:
[0008] Step A1, stirring ethyl orthosilicate and 3-triethoxysilyl propionitrile in ethanol to form a mixed solution 1; stirring ammonia water and deionized water in ethanol to form a mixed solution 2; then ultrasonically dispersing nano-barium sulfate in ethanol, heating to 60-70° C., adjusting the pH to 9, and then slowly dripping the mixed solution 1 and the mixed solution 2, after the dripping is completed, maintaining the system temperature to continue the reaction for 2-4 hours, and then standing at room temperature for 24 hours, centrifuging, washing, and drying to obtain barium sulfate @ silicon dioxide nanomaterials;
[0009] Further, the dosage ratio of nano-barium sulfate, ethanol, mixed solution 1 and mixed solution 2 is (2.5-3.5) g: 50 mL: 50 mL: 50 mL, the dosage ratio of ethyl orthosilicate, 3-triethoxysilylpropionitrile and ethanol in mixed solution 1 is (0.2-0.4) g: (0.05-0.15) g: 50 mL, and the dosage ratio of ammonia water, deionized water and ethanol in mixed solution 2 is (0.3-0.7) g: 10 mL: 40 mL;
[0010] Step A2, dispersing 3-5g of barium sulfate@silicon dioxide nanomaterial in 50mL of 48wt% sulfuric acid solution, raising the system temperature to 80-90°C, refluxing for 2-3h under stirring conditions, and after the reaction is completed, centrifuging, washing, and drying to obtain a reinforced filler;
[0011] The modified hyperbranched polyether is prepared by the following steps:
[0012] Step B1, add 3-(1H,1H,5H-octafluoropentyloxy)-1,2-propylene oxide and sodium hydroxide into ethanol and mix evenly, then add melamine, and stir at room temperature for 3 hours. After the reaction is completed, distill under reduced pressure to obtain an intermediate;
[0013] Further, in step B1, the usage ratio of 3-(1H,1H,5H-octafluoropentyloxy)-1,2-propylene oxide, sodium hydroxide, ethanol and melamine is (0.02-0.04) mol: (0.2-0.5) g: 50 mL: (0.02-0.04) mol;
[0014] Step B2, adding the intermediate and potassium hydroxide to a reactor, raising the system temperature to 90-100°C, adding propylene oxide under nitrogen conditions, and then raising the system temperature to 110°C, maintaining the temperature for reaction for 3-5h, then adding ethylene oxide, raising the system temperature to 120°C, and continuing the reaction for 4-6h. After the reaction is completed, adding acetic acid and stirring for 30min, vacuum filtering, and obtaining a hyperbranched polyether;
[0015] Furthermore, in step B2, the usage ratio of the intermediate, potassium hydroxide, propylene oxide, ethylene oxide and acetic acid is (0.05-0.15) mol: (0.005-0.015) mol: (0.3-0.6) mol: (0.25-0.5) mol;
[0016] Step B3, adding a hyperbranched polyether, methyl methacrylate, dibutyltin dilaurate and p-hydroxyanisole into a reactor, slowly heating to 120° C. under stirring, and maintaining the top temperature of the fractionation column at 55-65° C., keeping the reaction for 2-5 hours, and after the reaction is completed, performing reduced pressure distillation to obtain a modified hyperbranched polyether;
[0017] Furthermore, in step B3, the usage ratio of the hyperbranched polyether, methyl methacrylate, dibutyltin dilaurate and p-hydroxyanisole is (3-5) g: (1-2) g: (0.01-0.02) g: 0.001 g.
[0018] A method for preparing an optical adhesive for connecting an optical module in a high-speed optical module comprises the following steps:
[0019] Step S1, weighing raw materials according to weight, adding bisphenol A epoxy resin, modified hyperbranched polyether, photoinitiator, active diluent, reinforcing filler, antioxidant and polymerization inhibitor into a reactor, stirring and mixing evenly, which is recorded as a mixture;
[0020] Step S2, adding a curing agent to the above mixture, mixing evenly under vacuum and light-proof conditions, and then centrifuging and degassing to obtain an optical adhesive.
[0021] Beneficial effects of the present invention:
[0022] The optical adhesive of the present invention uses epoxy resin as the base resin, which has low volatility, high bonding strength, good durability and low curing shrinkage. The reinforcing filler introduced further reduces the shrinkage of the base and improves the transparency of the optical adhesive after curing. The introduction of the modified hyperbranched polyether reduces the refractive index of the base, and the introduction of the polyether chain segment also improves the flexibility of the base. In addition, the optical adhesive is cured by combining ultraviolet light and heat, which has the advantages of fast curing speed and good adhesion.
[0023] In the reinforcing filler, nano barium sulfate is first used as the filler base, and ethyl orthosilicate and 3-triethoxysilyl propionitrile are used as raw materials for synthesizing the silica coating layer to obtain barium sulfate@silica nanomaterials; then the nanomaterial is placed under acidic conditions for reflux treatment, so that the nitrile group on the surface of silica is hydrolyzed into carboxyl groups to obtain carboxylated nanomaterials. The addition of reinforcing fillers significantly reduces the shrinkage rate of epoxy resin after curing, because after the filler enters the matrix, it can increase the viscosity of the epoxy resin and reduce its fluidity through the filling effect, thereby inhibiting the shrinkage of the optical adhesive after curing; the carboxyl functional groups contained on its surface improve the dispersibility of the filler in the matrix, help prevent particle agglomeration, maintain the uniform distribution of particles, improve the stability of particles, and further reduce the curing shrinkage rate of the matrix; in addition, the synergistic effect between nano barium sulfate and the silica coating improves the transparency of the matrix, so that the optical adhesive still has a high transparency after curing; in addition, barium sulfate is introduced into the optical adhesive as the base of the filler, which also improves the toughness of the matrix.
[0024] In the modified hyperbranched polyether, the epoxy group in 3-(1H, 1H, 5H-octafluoropentyloxy)-1, 2-propylene oxide reacts with the amino group in melamine to generate an intermediate with a fluorine-containing chain segment; the intermediate is used as a starting material, and propylene oxide and ethylene oxide are used as raw materials to synthesize the hyperbranched polyether; the terminal hydroxyl group contained in the hyperbranched polyether is used to undergo an ester exchange reaction with the ester group in methyl methacrylate, thereby obtaining a modified hyperbranched polyether containing a double bond structure. After the modified hyperbranched polyether is introduced into the matrix, the refractive index of the matrix is reduced, which helps to reduce light loss and maintain good optical properties, and also improves the flexibility of the matrix; the reduction in refractive index is due to the low refractive index of the polyether itself, and then the introduction of melamine with a low refractive index into the polyether structure further reduces the refractive index of the matrix. At the same time, the presence of the fluorine-containing segment in the polyether also reduces the refractive index of the matrix. This is because the fluorine atoms in the fluorine-containing segment are distributed along the carbon chain spirally, tightly wrapping the entire carbon chain. This "shielding" effect makes it difficult for light waves to penetrate the polymer, thereby reducing the refractive index of the matrix; the introduction of the hyperbranched structure improves the compatibility of the polyether in the matrix, and at the same time, the terminal hydroxyl groups in the polyether can react with the epoxy resin, thereby introducing the flexible polyether segment into the epoxy resin main chain, and improving the flexibility of the epoxy resin matrix; in addition, the terminal double bonds in the modified hyperbranched polyether can also participate in the ultraviolet light curing reaction of the matrix, thereby improving the light curing speed of the matrix. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The reagents in the examples and comparative examples were purchased from the following manufacturers:
[0027]
[0028] Example 1
[0029] The reinforcing filler is prepared by the following steps:
[0030] Step A1, 0.2g of tetraethyl orthosilicate and 0.05g of 3-triethoxysilylpropionitrile were stirred in 50mL of ethanol to form a mixed solution 1; 0.3g of ammonia water and 10mL of deionized water were stirred in 40mL of ethanol to form a mixed solution 2; then 2.5g of nano-barium sulfate was ultrasonically dispersed in 50mL of ethanol, and heated to 60°C, and the pH was adjusted to 9, and then 50mL of the mixed solution 1 and 50mL of the mixed solution 2 were slowly added dropwise, and after the addition was completed, the system temperature was maintained to continue the reaction for 2h, and then the mixture was allowed to stand at room temperature for 24h, centrifuged, washed, and dried to obtain barium sulfate@silicon dioxide nanomaterials;
[0031] Step A2, dispersing 3 g of barium sulfate@silicon dioxide nanomaterial in 50 mL of 48 wt% sulfuric acid solution, raising the system temperature to 80° C., refluxing for 2 h under stirring conditions, and after the reaction is completed, centrifuging, washing, and drying to obtain a reinforced filler;
[0032] The modified hyperbranched polyether is prepared by the following steps:
[0033] Step B1, add 0.02 mol of 3-(1H,1H,5H-octafluoropentyloxy)-1,2-propylene oxide and 0.2 g of sodium hydroxide into 50 mL of ethanol and mix well, then add 0.02 mol of melamine, and stir at room temperature for 3 hours. After the reaction is completed, distill under reduced pressure to obtain an intermediate;
[0034] Step B2, 0.05 mol of the intermediate and 0.005 mol of potassium hydroxide were added to the reactor, the system temperature was raised to 900 ° C, 0.3 mol of propylene oxide was added under nitrogen, and the system temperature was raised to 110 ° C, the temperature was maintained for 3 hours, and then 0.25 mol of ethylene oxide was added, the system temperature was raised to 120 ° C, and the reaction was continued for 4 hours. After the reaction was completed, acetic acid was added and stirred for 30 minutes, and vacuum filtered to obtain a hyperbranched polyether;
[0035] Step B3, add 3g of hyperbranched polyether, 1g of methyl methacrylate, 0.01g of dibutyltin dilaurate and 0.001g of p-hydroxyanisole to the reactor, slowly heat to 120°C under stirring conditions, and maintain the top temperature of the distillation column at 55°C, keep the reaction for 2h, and after the reaction is completed, distill under reduced pressure to obtain the modified hyperbranched polyether.
[0036] Example 2
[0037] The reinforcing filler is prepared by the following steps:
[0038] Step A1, 0.3g of tetraethyl orthosilicate and 0.1g of 3-triethoxysilylpropionitrile were stirred in 50mL of ethanol to form a mixed solution 1; 0.5g of ammonia water and 10mL of deionized water were stirred in 40mL of ethanol to form a mixed solution 2; then 3g of nano-barium sulfate was ultrasonically dispersed in 50mL of ethanol, and heated to 65°C, and the pH was adjusted to 9, and then 50mL of the mixed solution 1 and 50mL of the mixed solution 2 were slowly added dropwise, and after the addition was completed, the system temperature was maintained to continue the reaction for 3h, and then the mixture was allowed to stand at room temperature for 24h, centrifuged, washed, and dried to obtain barium sulfate@silicon dioxide nanomaterials;
[0039] Step A2, dispersing 4 g of barium sulfate@silicon dioxide nanomaterial in 50 mL of 48 wt% sulfuric acid solution, raising the system temperature to 85° C., refluxing for 2.5 h under stirring conditions, and after the reaction is completed, centrifuging, washing, and drying to obtain a reinforced filler;
[0040] The modified hyperbranched polyether is prepared by the following steps:
[0041] Step B1, add 0.03 mol of 3-(1H,1H,5H-octafluoropentyloxy)-1,2-propylene oxide and 0.35 g of sodium hydroxide into 50 mL of ethanol and mix well, then add 0.03 mol of melamine, and stir at room temperature for 3 hours. After the reaction is completed, distill under reduced pressure to obtain an intermediate;
[0042] Step B2, 0.1 mol of the intermediate and 0.01 mol of potassium hydroxide were added to the reactor, the system temperature was raised to 95°C, 0.45 mol of propylene oxide was added under nitrogen, and the system temperature was raised to 110°C, the temperature was maintained for 4 hours, and then 0.35 mol of ethylene oxide was added, the system temperature was raised to 120°C, and the reaction was continued for 5 hours. After the reaction was completed, acetic acid was added and stirred for 30 minutes, and vacuum filtered to obtain a hyperbranched polyether;
[0043] Step B3, add 4g of hyperbranched polyether, 1.5g of methyl methacrylate, 0.015g of dibutyltin dilaurate and 0.001g of p-hydroxyanisole to the reactor, slowly heat to 120°C under stirring conditions, and maintain the top temperature of the distillation column at 60°C, keep the reaction for 3.5h, and after the reaction is completed, distill under reduced pressure to obtain the modified hyperbranched polyether.
[0044] Example 3
[0045] The reinforcing filler is prepared by the following steps:
[0046] Step A1, 0.4g of tetraethyl orthosilicate and 0.15g of 3-triethoxysilylpropionitrile were stirred in 50mL of ethanol to form a mixed solution 1; 0.7g of ammonia water and 10mL of deionized water were stirred in 40mL of ethanol to form a mixed solution 2; then 3.5g of nano-barium sulfate was ultrasonically dispersed in 50mL of ethanol, and heated to 70°C, and the pH was adjusted to 9, and then 50mL of the mixed solution 1 and 50mL of the mixed solution 2 were slowly added dropwise, and after the addition was completed, the system temperature was maintained to continue the reaction for 4h, and then the mixture was allowed to stand at room temperature for 24h, centrifuged, washed, and dried to obtain barium sulfate@silicon dioxide nanomaterials;
[0047] Step A2, dispersing 5 g of barium sulfate@silicon dioxide nanomaterial in 50 mL of 48 wt% sulfuric acid solution, raising the system temperature to 90° C., refluxing for 3 h under stirring conditions, and after the reaction is completed, centrifuging, washing, and drying to obtain a reinforced filler;
[0048] The modified hyperbranched polyether is prepared by the following steps:
[0049] Step B1, add 0.04 mol of 3-(1H,1H,5H-octafluoropentyloxy)-1,2-propylene oxide and 0.5 g of sodium hydroxide into 50 mL of ethanol and mix well, then add 0.04 mol of melamine, and stir at room temperature for 3 hours. After the reaction is completed, distill under reduced pressure to obtain an intermediate;
[0050] Step B2, 0.15 mol of the intermediate and 0.015 mol of potassium hydroxide were added to the reactor, the system temperature was raised to 100 ° C, 0.6 mol of propylene oxide was added under nitrogen, and the system temperature was raised to 110 ° C, the temperature was maintained for 5 hours, and then 0.5 mol of ethylene oxide was added, the system temperature was raised to 120 ° C, and the reaction was continued for 6 hours. After the reaction was completed, acetic acid was added and stirred for 30 minutes, and vacuum filtered to obtain a hyperbranched polyether;
[0051] Step B3, add 5g of hyperbranched polyether, 2g of methyl methacrylate, 0.02g of dibutyltin dilaurate and 0.001g of p-hydroxyanisole to the reactor, slowly heat to 120°C under stirring conditions, and maintain the top temperature of the distillation column at 65°C, keep the reaction for 5h, and after the reaction is completed, distill under reduced pressure to obtain the modified hyperbranched polyether.
[0052] Example 4
[0053] A method for preparing an optical adhesive for connecting an optical module in a high-speed optical module comprises the following steps:
[0054] 25 parts of bisphenol A epoxy resin, 8 parts of modified hyperbranched polyether prepared in Example 1, 2 parts of triphenylsulfonium chloride, 3 parts of N-benzyldimethylamine, 10 parts of hydroxyethyl methacrylate, 8 parts of reinforcing filler prepared in Example 1, 0.5 parts of antioxidant 1010, and 0.2 parts of hydroquinone;
[0055] Step S1, weighing raw materials by weight, adding bisphenol A epoxy resin, modified hyperbranched polyether prepared in Example 1, triphenylsulfonium chloride, hydroxyethyl methacrylate, reinforcing filler prepared in Example 1, antioxidant 1010 and hydroquinone into a reactor, stirring and mixing evenly, and recording as a mixture;
[0056] Step S2, adding N-benzyldimethylamine to the above mixture, mixing evenly under vacuum and light-proof conditions, and then centrifuging and degassing to obtain the optical adhesive.
[0057] Example 5
[0058] A method for preparing an optical adhesive for connecting an optical module in a high-speed optical module comprises the following steps:
[0059] 30 parts of bisphenol A epoxy resin, 12 parts of modified hyperbranched polyether prepared in Example 2, 3 parts of triphenylsulfonium chloride, 4 parts of N-benzyldimethylamine, 15 parts of hydroxyethyl methacrylate, 10 parts of reinforcing filler prepared in Example 2, 0.8 parts of antioxidant 1010, and 0.3 parts of hydroquinone;
[0060] Step S1, weighing raw materials by weight, adding bisphenol A epoxy resin, modified hyperbranched polyether prepared in Example 2, triphenylsulfonium chloride, hydroxyethyl methacrylate, reinforcing filler prepared in Example 2, antioxidant 1010 and hydroquinone into a reactor, stirring and mixing evenly, and recording as a mixture;
[0061] Step S2, adding N-benzyldimethylamine to the above mixture, mixing evenly under vacuum and light-proof conditions, and then centrifuging and degassing to obtain the optical adhesive.
[0062] Example 6
[0063] A method for preparing an optical adhesive for connecting an optical module in a high-speed optical module comprises the following steps:
[0064] 35 parts of bisphenol A epoxy resin, 15 parts of the modified hyperbranched polyether prepared in Example 3, 4 parts of triphenylsulfonium chloride, 5 parts of N-benzyldimethylamine, 20 parts of hydroxyethyl methacrylate, 12 parts of the reinforcing filler prepared in Example 3, 10101 parts of antioxidant, and 0.5 parts of hydroquinone;
[0065] Step S1, weighing raw materials by weight, adding bisphenol A epoxy resin, modified hyperbranched polyether prepared in Example 3, triphenylsulfonium chloride, hydroxyethyl methacrylate, reinforcing filler prepared in Example 3, antioxidant 1010 and hydroquinone into a reactor, stirring and mixing evenly, and recording as a mixture;
[0066] Step S2, adding N-benzyldimethylamine to the above mixture, mixing evenly under vacuum and light-proof conditions, and then centrifuging and degassing to obtain the optical adhesive.
[0067] Comparative Example 1
[0068] This comparative example is an optical adhesive, which differs from Example 6 in that an equal amount of nano-silicon dioxide is used to replace the reinforcing filler prepared in Example 3, and the rest are the same.
[0069] Comparative Example 2
[0070] This comparative example is an optical adhesive, which differs from Example 6 in that an equal amount of polyethylene glycol (molecular weight of 400) is used to replace the modified hyperbranched polyether prepared in Example 3, and the rest are the same.
[0071] The optical adhesives prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:
[0072] Refractive index test: measured according to GB / T 6488-2008 standard;
[0073] Light transmittance test: measured according to GB / T 2410-2008 standard;
[0074] Shrinkage test: The shrinkage is determined by applying a release agent to a mold with a length × width × height of 100 mm × 10 mm × 1 mm, pouring the optical adhesive prepared in Examples 4-6 and Comparative Examples 1-2 into the mold, curing it under a UV lamp for 2 min, and then placing it in a 90°C oven to completely cure it. Take out the cured adhesive block and measure its length, and calculate its shrinkage according to the following formula: Linear shrinkage = (100-length after curing) / 100 × 100%, where the length after curing is expressed in mm;
[0075] Tensile strength test: The optical adhesive prepared in Examples 4-6 and Comparative Examples 1-2 was coated on a dumbbell-shaped mold made according to GB / T 1040, cured for 1 min using a UV 365nm curing machine at 574w, and then placed in an oven at 100°C for 30 min. After cooling to room temperature, the obtained samples were subjected to a tensile strength test according to GB / T 1040 standard.
[0076] The test results are shown in the following table:
[0077] ;
[0078] It can be seen from the above table that the adhesive prepared in the present application has a lower refractive index and curing shrinkage, a higher light transmittance and excellent bonding performance. Therefore, the application of this optical adhesive in high-speed optical modules has a good application prospect.
[0079] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An optical adhesive for connecting high-speed optical modules, characterized in that: The invention comprises the following raw materials in parts by weight: 25-35 parts of bisphenol A epoxy resin, 8-15 parts of modified hyperbranched polyether, 2-4 parts of photoinitiator, 3-5 parts of curing agent, 10-20 parts of active diluent, 8-12 parts of reinforcing filler, 0.5-1 parts of antioxidant and 0.2-0.5 parts of polymerization inhibitor; The reinforcing filler is prepared by the following steps: Step A1, ethyl orthosilicate and 3-triethoxysilyl propionitrile are stirred evenly in ethanol to form a mixed solution 1; ammonia water and deionized water are stirred evenly in ethanol to form a mixed solution 2; then nano barium sulfate is ultrasonically dispersed in ethanol, and heated to 60-70° C., the pH is adjusted to 9, and then the mixed solution 1 and the mixed solution 2 are slowly added dropwise, and after the addition is completed, the system temperature is maintained to continue the reaction for 2-4 hours, and then the mixture is allowed to stand at room temperature for 24 hours, centrifuged, washed, and dried to obtain barium sulfate@silicon dioxide nanomaterials; Step A2, dispersing 3-5g of barium sulfate@silicon dioxide nanomaterial in 50mL of 48wt% sulfuric acid solution, raising the system temperature to 80-90°C, refluxing for 2-3h under stirring conditions, and after the reaction is completed, centrifuging, washing, and drying to obtain a reinforced filler; The modified hyperbranched polyether is prepared by the following steps: Step B1, add 3-(1H, 1H, 5H-octafluoropentyloxy)-1, 2-propylene oxide and sodium hydroxide to ethanol and mix evenly, then add melamine, and stir at room temperature for 3 hours. After the reaction is completed, distill under reduced pressure to obtain an intermediate. The amount ratio of 3-(1H, 1H, 5H-octafluoropentyloxy)-1, 2-propylene oxide, sodium hydroxide, ethanol and melamine is (0.02-0.04) mol: (0.2-0.5) g: 50 mL: (0.02-0.04) mol; Step B2, adding the intermediate and potassium hydroxide to the reactor, raising the system temperature to 90-100°C, adding propylene oxide under nitrogen, and then raising the system temperature to 110°C, maintaining the temperature for reaction for 3-5h, then adding ethylene oxide, raising the system temperature to 120°C, and continuing the reaction for 4-6h. After the reaction is completed, adding acetic acid and stirring for 30min, vacuum filtering, and obtaining a hyperbranched polyether, wherein the amount ratio of the intermediate, potassium hydroxide, propylene oxide, ethylene oxide and acetic acid is (0.05-0.15) mol: (0.005-0.015) mol: (0.3-0.6) mol: (0.25-0.5) mol; Step B3, add hyperbranched polyether, methyl methacrylate, dibutyltin dilaurate and p-hydroxyanisole into a reactor, slowly heat to 120°C under stirring conditions, and maintain the temperature at the top of the distillation column at 55-65°C, keep the reaction for 2-5 hours, and after the reaction is completed, perform reduced pressure distillation to obtain a modified hyperbranched polyether, wherein the amount ratio of the hyperbranched polyether, methyl methacrylate, dibutyltin dilaurate and p-hydroxyanisole is (3-5) g: (1-2) g: (0.01-0.02) g: 0.001 g.
2. The optical adhesive for connecting high-speed optical modules according to claim 1, characterized in that: In step A1, the dosage ratio of nano-barium sulfate, ethanol, mixed solution 1 and mixed solution 2 is (2.5-3.5) g: 50 mL: 50 mL: 50 mL.
3. The optical adhesive for connecting high-speed optical modules according to claim 2, characterized in that: The dosage ratio of ethyl orthosilicate, 3-triethoxysilylpropionitrile and ethanol in the mixed solution 1 is (0.2-0.4) g: (0.05-0.15) g: 50 mL.
4. The optical adhesive for connecting high-speed optical modules according to claim 2, characterized in that: The dosage ratio of ammonia water, deionized water and ethanol in the mixed solution 2 is (0.3-0.7) g: 10 mL: 40 mL.
5. A method for preparing an optical adhesive for connecting inside a high-speed optical module according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, weighing raw materials according to weight, adding bisphenol A epoxy resin, modified hyperbranched polyether, photoinitiator, active diluent, reinforcing filler, antioxidant and polymerization inhibitor into a reactor, stirring and mixing evenly, which is recorded as a mixture; Step S2, adding a curing agent to the above mixture, mixing evenly under vacuum and light-proof conditions, and then centrifuging and degassing to obtain an optical adhesive.
